2010
DOI: 10.1111/j.1365-2753.2008.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Key interventions and outcomes in joint arthroplasty clinical pathways: a systematic review

Abstract: A set of key interventions and outcome measures is available to support joint arthroplasty clinical pathways. Team and service outcomes should be further addressed in practice and research. Meta-analysis on the outcome indicators should be performed. Future studies should more rigorously comply with existing reporting standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 44 publications
2
42
0
2
Order By: Relevance
“…A large cohort study of 6000 patients, comparing an ER arthroplasty cohort to a traditional control found that ER patients can reduce length of stay (LOS) and need for blood transfusion [15] . Others have corroborated these findings [12][13][14][15][16][17][18][19][20] . Other advantages include reduction of both 30-day incidence of myocardial ischaemic events (p = 0.03) and 30-day mortality (p = 0.03) [15] .…”
Section: Methodssupporting
confidence: 68%
See 2 more Smart Citations
“…A large cohort study of 6000 patients, comparing an ER arthroplasty cohort to a traditional control found that ER patients can reduce length of stay (LOS) and need for blood transfusion [15] . Others have corroborated these findings [12][13][14][15][16][17][18][19][20] . Other advantages include reduction of both 30-day incidence of myocardial ischaemic events (p = 0.03) and 30-day mortality (p = 0.03) [15] .…”
Section: Methodssupporting
confidence: 68%
“…Furthermore the use of a clinical pathway curtails unnecessary investigation. Three studies reported a statistically significant decrease in the cumulative number of gratuitous tests [13] . A multidisciplinary pre-operative assessment clinic, in which patients are assessed by an anaesthetic-led team, can limit unplanned intensive care unit (ICU) admissions, and reduce LOS on high dependency unit (HDU) and ICU, as well as decreasing mortality rates, for complex orthopaedic surgery patients [52] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, physiotherapists, like other orthopaedic clinicians, are involved in surveillance and monitoring of patients following joint arthroplasty. 15,16 As well as assessing clinical outcomes, this can involve assessment of radiological measurement scores, including the progression of osteoarthritic changes and osteolysis or joint loosening; the JPOS can be used to assess the former. Second, physiotherapists are now involved in triaging patients for surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Ved artrose i hofte-og kneledd er leddprotesekirurgi en godt dokumentert behandlingsmetode som på sikt fremmer smertelindring, bedret funksjonsevne og livskvalitet (1,2). Inngrepet medfører samtidig sterke postoperative smerter, og opptreningen krever optimal smertebehandling (3,4).…”
Section: Bakgrunnunclassified